Adaptasi Bisnis Umkm Dengan Penjualan Dan Promosi Daring Di Masa Pandemi Covid 19 - Emaya Kurniawati; Adijati Utaminingsih; Witjaksono Witjaksono (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
The Community Service Program that we will carry out is located in Wonolopo Village, Mijen District, Semarang with the target audience of herbal medicine business players. The main problem is that so far the herbal medicine business actors do not know about the importance of online marketing and promotion, especially during the covid 19 period.In the implementation of this service, the method used is counseling on how to process herbal medicine in a clean and hygienic manner as well as training on marketing and online or online promotions so that during the current covid 19 pandemic, herbal products from members of the Jamu Sumber Husodo community, Wonolopo Village are better known in the community who will later will have an impact on increasing sales.The purpose of this service activity is to provide knowledge and training about marketing and promotion on line or online by utilizing internet media.